2019
DOI: 10.1093/condor/duy002
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion of Ring-billed Gulls (Larus delawarensis) from recreational beaches using canid harassment

Abstract: Ring-billed Gull (Larus delawarensis) populations have dramatically increased throughout their geographic range with the largest concentrations in the Great Lakes region of Canada and the United States. Large populations of gulls cause conflict with humans at recreational beaches, where their effects on human health and safety include bacteria contamination from gull feces. We used border collies to harass and exclude gulls from beaches in summer 2012 and 2013, then measured gull numbers and Escherichia coli. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…coli into the water and could be a useful proxy if validated at specific sites. Mitigation methods such as canine harassment have been shown to reduce gull numbers on beaches and improve water quality. , …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…coli into the water and could be a useful proxy if validated at specific sites. Mitigation methods such as canine harassment have been shown to reduce gull numbers on beaches and improve water quality. , …”
Section: Discussionmentioning
confidence: 99%
“…Mitigation methods such as canine harassment have been shown to reduce gull numbers on beaches and improve water quality. 61,62 Poor water circulation likely factors into the degraded water quality at the current swimming area at South Shore Beach. Previous studies 28 and the long-term monitoring of the two concurrent beach areas presented here have demonstrated that E. coli levels are significantly lower in the proposed beach area compared with the current beach area.…”
Section: ■ Discussionmentioning
confidence: 99%